"A Ringer Was Used to Make the Killing": Horse Painting and Racetrack Corruption in the Early Depression-Era War on Crime. (14th December 2021) - MILLER, VIVIEN
Abstract : Peter Christian "Paddy" Barrie was a seasoned fraudster who transferred his horse doping and horse substitution skills from British to North American racetracks in the 1920s. His thoroughbred ringers were entered in elite races to guarantee winnings for syndicates and betting rings in the Prohibition-era United States. This case study of a professional travelling criminal and the challenges he posed for the Pinkerton National Detective Agency in the early 1930s war on crime highlights both the importance of illegal betting to urban mobsters and the need for broader and more nuanced critiques of Depression-era organized-crime activities and alliances.